Deletion of Mucosa‐Associated Lymphoid Tissue Lymphoma Translocation Protein 1 in Mouse T Cells Protects Against Development of Autoimmune Arthritis but Leads to Spontaneous Osteoporosis. Issue 12 (9th November 2019) - Gilis, Elisabeth; Gaublomme, Djoere; Staal, Jens; Venken, Koen; Dhaenens, Maarten; Lambrecht, Stijn; Coudenys, Julie; Decruy, Tine; Schryvers, Nadia; Driege, Yasmine; Dumas, Emilie; Demeyer, Annelies; et al.
Abstract : Objective: Mucosa‐associated lymphoid tissue lymphoma translocation protein 1 (MALT‐1) plays a crucial role in innate and adaptive immune signaling by modulating the threshold for activation of immune cells, including Treg cells. Therefore, MALT‐1 is regarded to be an interesting therapeutic target in several immune‐mediated diseases. The goal of this study was to examine the role of MALT‐1 in experimental animal models of rheumatoid arthritis (RA). Methods: MALT‐1 activation was assessed by measuring cleavage of the deubiquitinase CYLD in lymphocytes from mice with collagen‐induced arthritis (CIA). Furthermore, the impact of MALT‐1 deficiency on arthritis was evaluated in Malt1 KO mice with CIA or with collagen antibody–induced arthritis (CAIA). T cell–specific MALT‐1 deficiency was measured in mice with deletion of T cell–specific MALT‐1 ( Malt1 Tcell KO ), and the time‐dependent effects of MALT‐1 deficiency were assessed in mice with deletion of tamoxifen‐inducible T cell–specific MALT‐1 ( Malt1 iTcell KO ). Bone density was determined in MALT‐1–deficient mice using micro–computed tomography and femur‐bending tests. Reconstitution of Treg cells was performed using adoptive transfer experiments. Results: MALT‐1 activation was observed in the lymphocytes of mice with CIA. T cell–specific MALT‐1 deletion in the induction phase of arthritis (incidence of arthritis, 25% in control mice versus 0% in Malt1 iTcell KO mice; P < 0.05), but not in the effector phase of arthritis, completely protected mice against the development of CIA. Consistent with this finding, MALT‐1 deficiency had no impact on CAIA, an effector phase model of RA. Finally, mice with MALT‐1 deficiency showed a spontaneous decrease in bone density (mean ± SEM trabecular thickness, 46.3 ± 0.7 μm in control mice versus 40 ± 1.1 μm in Malt1 KO mice; P < 0.001), which was linked to the loss of Treg cells in these mice. Conclusion: Overall, these data in murine models of RA highlight MALT‐1 as a master regulator of T cell activation, which is relevant to the pathogenesis of autoimmune arthritis. Furthermore, these findings show that MALT‐1 deficiency can lead to spontaneous osteoporosis, which is associated with impaired Treg cell numbers.